Practical road safety auditing - Belcher, Martin; Proctor, Steve; Cook, Phil (ICE Publishing, 2015)
'Practical Road Safety Auditing' explores the systematic process for checking the safety of new and improved road schemes for the benefit of future road users.
Previous edition: 2008.
Keywords: Traffic safety -- Great Britain -- Auditing.; Traffic engineering -- Great Britain -- Auditing.; Roads -- Inspection -- Great Britain.; elektronické knihy; electronic books